Definition of blindness under National Programme for Control of Blindness: Do we need to revise it? - Vashist, Praveen (Indian J Ophthalmol, 2017)
A review appropriateness of the current definition of blindness under National Programme for Control of Blindness (NPCB), Government of India. Online search of peer-reviewed scientific published literature and guidelines using PubMed, the World Health Organization (WHO) IRIS, and Google Scholar with keywords, namely blindness and visual impairment, along with offline examination of reports of national and international organizations, as well as their cross-references was done until December 2016, to identify relevant documents on the definition of blindness. The evidence for the historical and currently adopted definition of blindness under the NPCB, the WHO, and other countries was reviewed. Differences in the NPCB and WHO definitions were analyzed to assess the impact on the epidemiological status of blindness and visual impairment in India. The differences in the criteria for blindness under the NPCB and the WHO definitions cause an overestimation of the prevalence of blindness in India. These variations are also associated with an over-representation of refractive errors as a cause of blindness and an under-representation of other causes under the NPCB definition. The targets for achieving elimination of blindness also become much more difficult to achieve under the NPCB definition. Ignoring differences in definitions when comparing the global and Indian prevalence of blindness will cause erroneous interpretations. We recommend that the appropriate modifications should be made in the NPCB definition of blindness to make it consistent with the WHO definition.